Identification of Potential Metabolites Mediating Bird's Selective Feeding on Prunus mira Flowers. (23rd June 2019) - Zhang, Shanshan; Ying, Hong; Pingcuo, Gesang; Wang, Shuo; Zhao, Fan; Cui, Yongning; Shi, Jian; Zeng, Hu; Zeng, Xiuli
Abstract : In peach orchards, birds severely damage flowers during blossom season, decreasing the fruit yield potential. However, the wild peach species Prunus mira shows intraspecific variations of bird damage, indicating that some of the wild trees have developed strategies to avert bird foraging. Motivated by this observation, we formulated the present study to identify the potential flower metabolites mediating the bird's selective feeding behavior in P. mira flowers. The birds' preferred (FG) and avoided (BFT) flowers were collected from wild P. mira trees at three different locations, and their metabolite contents were detected, quantified, and compared. The widely-targeted metabolomics approach was employed to detect a diverse set of 603 compounds, predominantly, organic acids, amino acid derivatives, nucleotide and its derivatives, and flavones. By quantitatively comparing the metabolite contents between FG and BFT, three candidate metabolites, including Eriodictiol 6-C-hexoside 8-C-hexoside-O-hexoside, Luteolin O-hexosyl-O-hexosyl-O-hexoside, and Salvianolic acid A, were differentially accumulated and showed the same pattern across the three sampling locations. Distinctly, Salvianolic acid A was abundantly accumulated in FG but absent in BFT, implying that it may be the potential metabolite attracting birds in some P. mira flowers. Overall, this study sheds light on the diversity of the floral metabolome in P. mira and suggests that the bird's selective feeding behavior may be mediated by variations in floral metabolite contents.